Exploring the dynamics of high-growth determinants for gazelle companies using interpretive structural modeling - Santos, M.; Ferreira, F.; Ferreira, N.; Ferreira, J.; Meidute-Kavaliauskiene, I. (Journal of Small Business and Enterprise Development, 2024)
Purpose: Gazelle companies are characterized by rapid growth in a short time. Identifying the determinants of this exponential expansion is important as these firms have a significant impact on the economy. They generate increased employment and investment by investors interested in new opportunities. Previous studies have failed to reach a consensus about what fosters high growth in gazelle companies as each firm’s geographical, political and economic context is different. The present research uses cognitive mapping and interpretive structural modeling (ISM) to overcome the limitations of prior investigations and identify factors that can potentially accelerate growth in gazelle companies. Design/methodology/approach: Two sessions were held with an expert panel with knowledge about and experience with these firms. In the first session, data were collected to create a group cognitive map, while the second meeting comprised ISM-based analyses of the high-growth determinants identified and the causal relationships between them. A final consolidation session was held to discuss the results with two members of the Committee for Central Region Coordination and Development (i.e., Comissão de Coordenação e Desenvolvimento Regional do Centro—a public entity that grants gazelle awards in Portugal). Findings: The analysis system created was tested, and the results demonstrate that the dual methodology used can increase our understanding of the dynamics of high-growth determinants and lead to more informed and potentially better evaluations of gazelle companies. Indeed, once high-growth determinants in gazelle companies are understood, this information can help other firms implement the same business model to achieve similarly rapid growth. The strengths and shortcomings of this new structured analysis model are also analyzed. Originality: The authors know of no prior work reporting the integrated use of cognitive mapping and ISM in this study context.